1994
DOI: 10.1007/bf01499173
|View full text |Cite
|
Sign up to set email alerts
|

Explanatory models of malingering: A prototypical analysis.

Abstract: Rogers (1990aRogers ( , 1990b proposed three models to explain why certain persons malinger mental illness: pathogenic, criminological, and adaptational. Highly experienced forensic experts (N = 320) performed prototypical ratings on attributes associated with each model; the highest ratings were given to the adaptational model. In addition, a principal components analysis provided initial empirical support for these three explanatory models. The relevance of these findings to theory and clinical practice is d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
88
0
4

Year Published

1998
1998
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 140 publications
(96 citation statements)
references
References 12 publications
4
88
0
4
Order By: Relevance
“…The pooled sample consisted of 298 participants of whom 57 (19%) were known to feign symptoms on the SIMS. Note that the base rate of malingering comes close to the 17% reported by Rogers et al (1994). Using a cutoff point of 16 for the SIMS total score, accuracy indices can be calculated from the data presented in Table 3.…”
Section: Predictive Accuracymentioning
confidence: 57%
See 1 more Smart Citation
“…The pooled sample consisted of 298 participants of whom 57 (19%) were known to feign symptoms on the SIMS. Note that the base rate of malingering comes close to the 17% reported by Rogers et al (1994). Using a cutoff point of 16 for the SIMS total score, accuracy indices can be calculated from the data presented in Table 3.…”
Section: Predictive Accuracymentioning
confidence: 57%
“…In the studies cited above, the base rate of malingering always circled around 50%. On the other hand, a survey among forensic experts (Rogers, Sewell, & Goldstein, 1994) estimated the base rate of malingering in forensic settings to be only 17%.…”
Section: Introductionmentioning
confidence: 99%
“…One study by Cornell and Hawk (1989) found that malingering was diagnosed in 8% of 314 pretrial evaluations. Rogers, Sewell, and Goldstein (1994) polled 320 experienced forensic evaluators and found that these professionals estimated they diagnosed malingering in approximately 15% of their cases. Further base rate data is needed to determine the frequency with which clinicians evaluating pretrial defendants make a malingering diagnosis.…”
Section: Diagnoses Among Forensic Referralsmentioning
confidence: 99%
“…Malingering is not infrequent: estimates range from 15% in the forensic setting to 7% in the non-forensic setting [19], with one study noting that resident psychiatrists working in the emergency room reported a strong suspicion of malingering in 13% of patients evaluated [20]. Supposing that it is possible to administer to all patients suspected of malingering psychological testing, e.g., MMPI, what is to be done with the psychiatrist's interview?…”
Section: Intuition In Psychiatrymentioning
confidence: 98%